British Public Widely Supports NATO and Narrowly Approves INF Deployment. - United States Information Agency. Office of Research.; Spencer, Charles S., Jr. (Tufts University. Tisch Library., 2019)
A USIA-sponsored survey conducted in Britain and six other NATO countries between May and early July 1984 shows that confidence in U.S. ability to deal responsibly with world problems has risen dramatically among Britons since December 1983.; Foreign Opinion Note N-9/11/84-B